(untitled) - Kennedy, Diane (Hoboken, N.J., 2007)
This guide from bestselling real estate authors de Roos and Kennedy shows you how to use tax-free retirement funds to invest in real estate. Using real estate IRAs, you can combine the tax benefits of retirement funds with the high rates of appreciation in the real estate market, growing your retirement investments by leaps and bounds. This handy book shows you how
Keywords: Real estate investment,Real estate investment,Retirement income,Đầu tư địa ốc; Taxation,United States; Planning; United States,United States